Monumental mosaics as places of memory in public spaces of Ukraine - Soklakov, Maksym (Ukrainian Cultural Studies, 2024)
Background. Modernist monumental mosaics as an intrinsic part of Soviet cultural heritage are ubiquitously present all over the urban environments of Ukraine. With rare exceptions, they remain predominantly unacknowledged as being valuable objects of cultural heritage. Many fine works of monumental art are already lost and others remain under constant threat. The precarious situation of modernist mosaics calls for a thorough reexamination of a complex situation with memory politics in Ukraine overall. The goal of this article is to explore the theoretical-methodological framework of memory studies for its applicability to the analysis of socio-cultural value of Soviet monumental modernist mosaics within the context of their destruction by the ongoing process of commercialization and decommunization of public spaces in post-socialist cities. The research objectives are to investigate the current status of modernist mosaics within contemporary Ukrainian heritage preservation discourse and conceptualize it within the memory studies framework.Methods. Case studies, narrative and textual analysis, interdisciplinary integration of cultural and memory studies, application of the "collective memory" approach, synthesis of "postmemory" and "places of memory" concepts.Results. Created by Ukrainian monumental artists of the Soviet period, modernist mosaics are already deeply embedded within the urban environment. Within the framework of memory studies, modernist mosaics may serve as 'places of memory' of that particular period of history and in that way contribute to its reinterpretation and further formation of the complete image of city memory and of inclusive memory politics of Ukraine.Conclusions. The theoretical-methodological framework of memory studies appears to be an appropriate tool for analysis of socio-cultural value of monumental mosaics. There is a necessity for further inquiries into this field and its further engagement in the development of Ukrainian heritage preservation discourse.
Keywords: Soviet architectural modernism; monumental mosaics; cultural heritage; memory politics; postmemory; contested heritage